Correlating the morphology of Anacardium occidentale L. fruits from 30 orchards with their physicochemical and nutritional properties - Dakuyo, Roger; Konaté, Kiessoun; Bazié, David; Sanou, Abdoudramane; Kaboré, Kabakdé; Sama, Hemayoro; Santara, Balmoussa; Konkobo, Frédéric Anderson; Dicko, Mamoudou Hama (Frontiers in Plant Science, 2022)
Cashew (Anacardium occidentale L.) is a cross-pollinating plant whose fruit consists of two parts, the nut, and the apple. In this study agro-morphological characteristics of cashew fruits were determined to establish relationships with their physicochemical and nutritional properties. Fruits were sampled from 30 orchards in Burkina Faso. The length, width, thickness, ight, yield, kernel output ratio (KOR), proximate composition, specific minerals, phenolic compounds, and anti-nutritional factors were assessed. The ratio of apple mass versus nut one was about 12.24±1.24. Kernels are very rich in proteins, fat, total phenolic compounds, and flavonoids, with average contents of 22.84±1.25 g/100 g, 51.65±2.54 g/100 g, 9.78±2.15 mg GAE/g and 6.24±12.15 mg QE/g, respectively. Apples contained significant amounts of some minerals such as K, P, Cl, and Mg with contents of 611.24±14.5 mg/100 g, 418.24±16.47 mg/100 g, 332.24±10.54 mg/100 g, and 224.95±13.15 mg/100 g, respectively. Principal component analyses showed three groups for apples and kernels. Mineral and phytate contents were positively correlated to cashew apples while phenolic compounds and tannins were strongly correlated with walnuts. These data provided direct relationships between the content of cashew kernels, apples, and their agro-morphological characteristics. Furthermore, the morphological characteristics of cashew fruits could be linked with their nutritional values.